SIMULTANEOUS ESTIMATION OF FEBUXOSTAT AND NAPROXEN IN SYNTHETIC MIXTURE BY REVERSE PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY METHOD - Thula, M. s. Krupa; Reshma A., Patel; Maheshwari, Dilip G. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: To develop simple, precise, rapid, and accurate RP-HPLC method for the simultaneous estimation of Febuxostat and Naproxen in synthetic mixture. To perform complete validation of newly developed analytical methods as per ICH(Q2) R1 [32] Guideline. Methods: In RP-HPLC method for Febuxostat and Naproxen, chromatographic separation was carried out on Shimandzu LC-20AT, Hypersil BDS column (250mm x 4.6mm, 5 μm) using mobile phase ACN: Methanol: Phosphate Buffer (50:35:15 v/v) pH 5, detected at 288 nm, with flow rate 1.0ml/min and injection volume 20 μL. Results: For RP- HPLC Linearity of Febuxostat and Naproxen were found to be 4 – 12 μg/ml and 25 - 75 μg/ml respectively. For both the developed and validated methods the %RSD was found to be less than 2% and the % recovery was found to between 98-102 %. Conclusion: The developed and validated method was found to be simple, accurate, economical, robust and reproducible. There was no interference of any diluent and excipient in the determination of drugs from synthetic mixture. So, the method can be successfully applied for routine Quality control analysis.